2023
DOI: 10.1021/acs.est.3c04132
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Chloride and Sulfate Ions in Controlling Cadmium Transport in a Soil-Rice System as Evidenced by the Cd Isotope Fingerprint

Songxiong Zhong,
Liping Fang,
Xiaomin Li
et al.

Abstract: Anions accompanying inorganic fertilizers, such as chloride and sulfate ions, potentially affect the solubility, uptake, and transport of Cd to rice grains. However, the role of anions in controlling Cd transport in the soil−soil solution−Fe plaque−rice plant continuum remains poorly understood. Cd isotope ratios were applied to Cd-contaminated soil pots, hydroponic rice, and adsorption experiments with or without KCl and K 2 SO 4 treatments to decipher transport processes in the complex soil−rice system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Strategies such as supplying Zn fertilizers and drainage regimes are generally adopted in practice; however, the molecular mechanisms underlying their uptake and transport have not been well elucidated owing to the complicated processes of Zn transport from soils to grains (Weiss et al, 2005;Jouvin et al, 2012;Tang et al, 2012). A combination of isotope and gene analyses may provide robust evidence for elucidating the underlying processes during uptake and transport (Zhong et al, 2021;2023). This study revealed that drainage regimes and Zn fertilizer could downregulate the ZIP family genes but upregulate OsHMA2 in roots and node I relative to ooding regimes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies such as supplying Zn fertilizers and drainage regimes are generally adopted in practice; however, the molecular mechanisms underlying their uptake and transport have not been well elucidated owing to the complicated processes of Zn transport from soils to grains (Weiss et al, 2005;Jouvin et al, 2012;Tang et al, 2012). A combination of isotope and gene analyses may provide robust evidence for elucidating the underlying processes during uptake and transport (Zhong et al, 2021;2023). This study revealed that drainage regimes and Zn fertilizer could downregulate the ZIP family genes but upregulate OsHMA2 in roots and node I relative to ooding regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The soil samples were extracted using 0.1 M CaCl 2 and 0.1 M HCl to attain exchangeable and acidic Zn in the soil (Arnold et al, 2015;Aucour et al, 2015). To extract the iron plaque on roots at the jointing stage, a mixture of 0.5 M HCl and 0.1 M HCl was added into a vial containing speci c root amounts, followed by ultrasonication with 15 min per treatment twice (Zhong et al, 2021;2023;2024). A proper amount of soil or rice tissue samples were added with a mixture of HNO 3 and HF and digested in a high-performance Milestone microwave digestion system (ETHOS UP, Italy) at 150 ℃ for 8 h, and then dried at 160 ℃ to remove the remaining uorine.…”
Section: Sample Pretreatment and Mass Analysismentioning
confidence: 99%
“…In some cases, Cl − induces a higher Cd removal [20][21][22][23], while it seems to decrease Cd retention in other studies [24][25][26][27]. A recent publication states the importance of chloride and sulfate on the migration of Cd in soils and its subsequent uptake by plants [28].…”
Section: Introductionmentioning
confidence: 98%
“…It not only acts as a barrier resistant to the upward transport of pollutants but also acts as a producer of interfacial reactive oxygen species (ROS) for pollutant degradation. For example, iron plaque on rice root surface prevented the migration of Cd and As, and ROS on the iron plaque surface were responsible for the degradation of propane and atrazine . However, iron plaque is known to exist only on the root surfaces of wetland plants such as Oryza sativa, Phragmites austra, Salix jiangsuensis, Spartina alterniflora, and Kandelia obovate due to the demanding submerged anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%